Les nouvelles politiques industrielles : Le cas des télécommunications - Albert, Alain; Crener, Maxime (Études internationales, 1983)
After showing the dynamic character of the world market of telecommunications equipment, the authors analyze the main factors which have contributed to the elaboration of the industrial structure in this field. Particular stress is laid on the role played by technological evolution as driving force of the industrial reorganization which is taking place right now in the field. This reorganization movement on a world scale has sometimes given rise, in industrial policy, to totally different behaviours from governments. Thus, the strategies of the Japanese and French branches are countered by measures taken by the US Government to deregulate and liberalize the market. The authors conclude by pointing out that, given the limited means at its disposal and faced with an international market of electronics threatened by competition from the Newly Industrialized Countries, there is a need for Canada to adopt a differential strategic approach which will allow it to acceed to technological sovereignty and to counter the delocalisation process which profit the NIC of South-East Asia.